Medical Application of Functional Biomaterials (2nd Edition) (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint presents a curated selection of recent scientific contributions exploring the medical applications of functional biomaterials. As research in this interdisciplinary field progresses, the focus continues to shift toward enhancing the safety, performance, and biological compatibility of advanced materials used in medical devices. The articles featured here reflect a wide range of innovations—from strategies to evaluate immune responses to the development of biocompatible materials for implants. Particular attention is given to topics such as dental biomaterials, biomedical nanoparticles, and the use of naturally derived substances in therapeutic applications. Collectively, these studies highlight the ongoing efforts to bridge the gap between material science and clinical practice, offering new insights into the complex interactions between engineered materials and biological systems. This compilation is valuable for researchers, engineers, and clinicians interested in the current landscape and future perspectives of functional biomaterials in medicine.